Epithelial polarity: the ins and outs of the fly epidermis. - Knoblich, J.A. (Current Biology, 2000)
Epithelial cells must polarize and establish apical and basolateral membrane domains during development. Recent experiments have shed light on how apical-basal polarity is generated during cellularization in Drosophila, when around 6000 epithelial cells are created synchronously from a syncytium.